ANALISIS METODE PENELITIAN KUANTITATIF DALAM MANAJEMEN PENDIDIKAN ISLAM - Asy'ari Asy'ari; Dwi Ajeng Maulidya Makalao; Irawan Irawan (LP2M IAIN Sultan Amai Gorontalo, 2023)
This study aims to improve understanding of quantitative research methods in the context of Islamic education management. The research method used is a qualitative literature study with a descriptive approach. The use of quantitative methods in Islamic education management research improves understanding of the factors that influence effectiveness. Challenges include a lack of understanding of the method, incomplete data, unrepresentative samples, and limited resources. The application of information and communication technology supports innovative approaches in Islamic education management. Quantitative methods help to understand the factors affecting effectiveness in Islamic education. Challenges include a lack of understanding, a lack of data, representative samples, and limited resources. The use of technology provides innovation, but challenges include access and practitioner skills.